RISK FACTORS FOR SEVERE PREECLAMPSIA AT DR. WAHIDIN SUDIRO HUSODO HOSPITAL MOJOKERTO CITY IN 2021-2022 - Nurhayati, Enok Tuti; Budiono, Dwi Izzati; -, Aditiawarman (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Background: Preeclampsia and eclampsia are major causes of morbidity and mortality during the perinatal period. The change from preeclampsia to severe preeclampsia can progress rapidly. The case of severe preeclampsia in Dr. Wahidin Sudiro Husodo Hospital, is very high. Purpose: To analyze the risk factors for severe preeclampsia at Dr. Wahidin Sudiro Husodo Hospital, Mojokerto City. Subjects and Methods: This study was conducted using an observational analytic quantitative method with an case control design. The sampling method used consecutive sampling. This study involved a total of 150 samples from two groups, consisting of pregnant women and laboring women. Results: The variables that had a significant relationship with the incidence of severe preeclampsia were age variables (p-value: 0.000; OR: 4.330; CI: 1.972-9.507), history of obesity (p-value: 0.000; OR: 15.460; CI: 5.255-45.483), history of preeclampsia (p-value: 0.001; OR: 7.579; CI: 2.127-27.006), history of diabetes mellitus (p-value: 0.012; OR: 11.385; CI: 1.419-91.352), and history of chronic hypertension (p-value: 0.000; OR: 6.945; CI: 2.931-16.456) were all significantly associated with the incidence of severe preeclamsia . the variables of age, history of obesity, and history of chronic hypertension met the final modeling in multivariate analysis. Conclusion: The history of obesity being the most dominant variable.